A Study of Urinary Tract Infections Prevalence, Antibiotics Resistance, and Biofilm Formation Capability of the Bacterial Causal Agents - Safa Ali Naji; Halah Abdulkhaliq Awadh (Tikrit Journal of Pure Science)
The aim of this study was to evaluate the incidence of Urinary Tract Infections (henceforth, UTI) in Salahadin governorate/ Iraq, identify the causative agents, their antibiotic sensitivity and their ability to form biofilms. Such studies are mandatory to determine the empirical therapy of such cases. A total of 650 urine samples were collected. Then, 250 samples were cultured, as suspected of having UTI, of which 193 samples (77.2 %) showed positive culture, while 57 samples (22.8 %) were negative cultures. Gram-positive bacteria were the predominant cause of UTI as represented by (66.7%), while Gram-negative species were found in (33.3%). Staphyloccus spp. bacteria were the predominant Gram-positive genus to isolate from UTI patients, while E. coli was the predominant species among Gram-negative bacteria. The isolates were tested for antibiotic susceptibility and biofilm formation. The most effective antibiotics tested on the Gram-positive isolates were Nitrofurantoin followed by Chloramphenicol (with resistance of 19% and 20%, respectively), whereas the least effective one was Azithromycin (with 64% resistance). As for the most effective antibiotic tested on the Gram-egative isolates, it was Amikacin (having only 8% resistance), while the least effective one was Erythromycin (with 98% resistance). Biofilm detection was performed by employing Congo red agar (CRA) method and microtiter plate (MTP) assay. The results showed that by using CRA method, about 81.3% of isolates were biofilm formers. While 96.7% of isolates were detected as biofilm formers by using MTP assay. Generally, biofilm formation was more predominant among Gram-positive isolates than Gram-negative ones.